2017
DOI: 10.15406/unoaj.2017.05.00171
|View full text |Cite
|
Sign up to set email alerts
|

Review Article - MCP-1: A Potential Target for Diabetic Microvascular Complications?

Abstract: MCP-1 is a potent chemokine with the ability to mobilize and stimulate leucocytes, especially monocytes and macrophages. It is increasingly recognized as an important player in the inflammatory process that is diabetic nephropathy. In this article, we describe its role in inducing renal injury by outlining key studies in animal models and clinical studies of diabetic nephropathy, its association with diabetic retinopathy, as well as its potential use as a prognostic biomarker and as a therapeutic target in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These, in turn, are associated with increased expression of adhesion molecules and synthesis of pro-inflammatory cytokines, leading to hyperfiltration and glomerular lesions, typical of DKD. 75,76…”
Section: Introductionmentioning
confidence: 99%
“…These, in turn, are associated with increased expression of adhesion molecules and synthesis of pro-inflammatory cytokines, leading to hyperfiltration and glomerular lesions, typical of DKD. 75,76…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the levels of chemokines had significantly increased in patients with DR and the MCP‐1 was the most frequently added chemokine in serum and vitreous levels (Elner et al 1995; El‐Asrar et al 1997; Capeans et al 1998). It should be noted that the MCP‐1 plays a pivotal role in vascular inflammation through induction, activation, and recruitment of monocytes and macrophages (Yap et al 2017). In this regard, Rangasamy et al showed that the knockout of the MCP‐1 gene in diabetic mice had an inhibitory effect on modifications of the BRB (Rangasamy et al 2012).…”
Section: Therapeutic Targets and Clinical Outcomesmentioning
confidence: 99%
“…Monocyte chemoattractant protein-1 (MCP-1) is a strong chemokine that is capable of stimulating leucocytes, particularly macrophages and monocytes. A recent study demonstrated that MCP-1 plays an important role in the inflammatory process in diabetic nephropathy (Yap 2017 ).…”
Section: Introductionmentioning
confidence: 99%